Challenges and prospects of applications of total quality management in higher education institutes - Islam, Rafikul (2015)
In modern times, universities have become an independent source of knowledge which take the responsibility of leading the nation, defend its possessions and encounter the challenges ahead, build its economic and intellectual capital based on a more genuine, academic and systematic grounds, and improve its lead to cope with the advancement in science and technology. Indeed, universities are one of the essential entities for change in the social, intellectual, and political realm as society heads to the future. Currently, there are many Saudi public universities are implementing total quality management (TQM) programs to improve their quality education system, but they are still struggling to reap the desired benefits. Therefore, the aim of this study is to analyze the current situation of public universities in Saudi Arabia, in view of the implementation of TQM, and to explore the challenges and resolutions of TQM implementation in Saudi public universities in order to achieve higher academic excellence. This study applied Quality Function deployment (QFD) model, in order to identify the most critical challenges and resolutions of TQM implementation in enhancing the quality of education in Saudi public universities. The findings of this study contributes to the existing body of knowledge in the field of TQM, as well as providing insight to public universities of Saudi Arabia in order to achieve higher academic excellence.